UV-induced-OCH3 Rotamerization in a Matrix-Isolated Methoxy-Substituted Ortho-Hydroxyaryl Schiff Base - Sıdır, İsa; Sıdır, Yadigar Gülseven; Gobi, Sandor; Berber, Halil; ILDIZ, GÜLCE ÖĞRÜÇ; Fausto, Rui (Springernature, 2022)
A new methoxy-substituted ortho-hydroxyaryl Schiff base, 4-(3-methoxy-2-hydroxybenzylidene-amino) phenol was synthesized from 4-aminophenol and 2-hydroxy-3-methoxybenzaldehyde in methanol solution and characterized by H-1-NMR, C-13-NMR and infrared spectroscopies and elemental analysis. The compound was isolated in a cryogenic (10 K) argon matrix, and the analysis of the infrared spectrum of the matrix-isolated compound revealed that it corresponds to the E-enol-imine isomeric form, with 3 different conformers being present in the matrix. These conformers share as common structural features the conformation of the free hydroxyl group (trans relatively to the para-substituent of the ring) and the presence of an OH center dot center dot center dot N intramolecular H-bond involving the methoxy-substituted phenol ring and the azomethine bridge, while they differ in the orientation of the methoxy-substituent group. The structures and relative energies of the conformers of the molecule, and relevant barriers for their interconversion were obtained through quantum chemical calculations, which were also used to calculate the infrared spectra of the different forms. Calculations were also carried out for the higher-energy Z-enol-imine and keto-amine forms of the compound. Upon UV (230 nm) irradiation, -OCH3 rotamerization was observed, leading to conversion of the lowest energy conformer, where the methoxy group is aligned with the plane of the ring, into the other two conformers initially present in the matrix, in which the OCH3 group is out-of-the-plane of the ring. As for other phenolic compounds previously studied, spontaneous quantum mechanical tunneling conversion of the cis-OH conformers present in the gas-phase into the three observed conformers was found to take place during matrix deposition.
Keywords: UV-induced –OCH3 Rotamerization; 4-(3-Methoxy-2-hydroxy-benzylideneamino) Phenol; Matrix Isolation; Tunneling Decay; DFT(B3LYP)/6-311++G(d.p) Calculations